Airborne fungal spores at the Belgrad forest near the city of Istanbul (Turkey) in the year 2001 and their relation to allergic diseases - (:unkn) unknown (WILEY, 2003)
The aim of this study was to investigate the relationship between airborne fungal spores and allergic diseases; for this reason, the airborne fungal spores that were obtained from five different locations of Belgrad Forest were isolated, determined and studied quantitatively. Totally 120 samples were examined by using the Petri Plate Gravitational Method, and fungi obtained from these samples were isolated and 600 colonies were counted. By identification of these isolations, 13 genera (Mucor, Rhizopus, Absidia, Aspergillus, Penicillium, Trichoderma, Trichothecium, Stemphylium, Cladosporium, Alternaria, Ulocladium, Aureobasidium and Fusarium), 25 species and 10 different sterile fungi were determined. The identifications of these fungi were made according to their microscopic, macromorphological features and references.
Keywords: AIR; ATMOSPHERE; ASTHMA; CHILDHOOD; QUARTER; LONDON; DAVOS; AREA